The Influence of Heavy Metals and Water Parameters on the Composition and Abundance of Water Bugs (Insecta: Hemiptera) in the Kerian River Basin, Perak, Malaysia - Nur Adibah Mohd Ishadi; Che Salmah Md Rawi; Abu Hassan Ahmad; Nurul Huda Abdul (Tropical Life Sciences Research, 2014)
The hemipteran (Insecta) diversity in the upper part of the Kerian River Basin was low with only 8 families and 16 genera recorded at 4 study sites from 3 rivers. Water bug composition varied among sampling sites (Kruskal-Wallis ?² = 0.00, p<0.05) but was not affected by wet-dry seasons (Z = 0.00, p>0.05). All recorded water parameters were weakly associated with generic abundance but the biochemical oxygen demand (BOD), chemical oxygen demand (COD), Water Quality Index (WQI) and heavy metals (zinc and manganese) showed relatively strong positive or negative relations with hemipteran diversity and richness (H’ and R2). Within the ranges of measured water parameters, the WQI was negatively associated with hemipteran diversity and richness, implying the tolerance of the water bugs to the level of pollution encountered in the river basin. Based on its highest abundance and occurrence (ISI), Rhagovelia was the most important genus and along with Rheumatogonus and Paraplea, these genera were common at all study sites. In conclusion, habitat availability and suitability together with some environmental parameters influenced the abundance and composition of hemipterans in this river basin. Kepelbagaian hemipteran (Insekta) di bahagian atas lembangan Sungai Kerian adalah rendah dengan hanya 8 famili dan 16 genus direkod dari 4 kawasan penelitian pada 3 sungai. Komposisi mereka berbeza secara signifikan antara kawasan penelitian (Kruskal-Wallis ?² = 0.00, p<0.05) tetapi tidak dipengaruhi oleh musim hujan dan kering (Z = 0.00, p>0.05). Semua parameter air yang direkod berkait lemah dengan kelimpahan genus tetapi permintaan oksigen biokimia (BOD), permintaan oksigen kimia (COD), indeks kualiti air (WQI) dan logam berat (zink dan mangan) menunjukkan hubungan negatif atau positif yang hampir kuat terhadap kepelbagaian dan kekayaan hemipteran (H’ and R2). Rangkuman julat parameter air yang diukur, WQI adalah berkait secara negatif dengan kepelbagaian dan kelimpahan hemipteran yang menunjukkan toleransi mereka terhadap tahap pencemaran yang terdapat di lembangan sungai ini. Berdasarkan kepada kelimpahan dan kekerapannya yang tinggi (ISI) Rhagovelia adalah genus yang paling penting dan bersama dengan Rheumatogonus dan Paraplea, mereka sangat banyak ditemui di kawasan penelitian. Sebagai kesimpulan, keterdapatan dan kesesuaian habitat serta beberapa parameter persekitaran mempengaruhi kepelbagaian dan kelimpahan hemipteran di lembangan sungai ini.